(untitled) (Web of Teachers: Inderscience Research, 2025)
This article discusses the heritage of Uzbek national music, the development of traditional Maqom art, and the prospective projects. They analyzed the magic of the song “Shashmaqom”, its appeal to the soul, its positive effect on the spirituality of the youth.